Barriers to Mammography Among Inadequately Screened Women. (February 2015) - Stoll, Carolyn R. T.; Roberts, Summer; Cheng, Meng-Ru; Crayton, Eloise V.; Jackson, Sherrill; Politi, Mary C.
Mammography use has increased over the past 20 years, yet more than 30% of women remain inadequately screened. Structural barriers can deter individuals from screening, however, cognitive, emotional, and communication barriers may also prevent mammography use. This study sought to identify the impact of number and type of barriers on mammography screening status, and to examine whether number and type of barriers are different for never-screened and off-schedule women. A total of 182 women aged 40 years or older completed a computer kiosk facilitated survey as part of a larger patient navigator intervention. Logistic regression analysis indicated that breast cancer knowledge predicted whether a woman had ever had a mammogram (odds ratio [ OR ] = 1.04, 95% confidence interval [CI] = 1.02-1.06, p = .0003), while the number of emotional, structural, and communication barriers predicted whether a woman was on-schedule for mammograms ( OR = 0.79, 95% CI = 0.65-0.95, p = .0127). The results suggest that to increase the use of mammography at recommended regular intervals, interventions should be tailored toward current screening status.